Perceptions of affirmative action: An empirical study - Trevor Amos; Richard Scott; J. William; Judith Scott (South African Journal of Business Management, 1996)
Private and public South African employers have instituted affirmative action policies meant to provide employment opportunities to Black South Africans. A body of literature suggests that because of affirmative action policies Black hopes have been raised while Whites view such policies as having a negative impact on their opportunities. However, no extant literature details an empirical investigation of these suggestions. Therefore, this study focusses on the affirmative action perceptions held by 350 South African university commerce students.
Keywords: 650